2015
DOI: 10.1186/s12864-015-1726-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of in vitro and in vivo disconnects using transcriptomic data

Abstract: BackgroundIntegrating transcriptomic experiments within drug development is increasingly advocated for the early detection of toxicity. This is partly to reduce costs related to drug failures in the late, and expensive phases of clinical trials. Such an approach has proven useful both in the study of toxicology and carcinogenicity. However, general lack of translation of in vitro findings to in vivo systems remains one of the bottle necks in drug development. This paper proposes a method for identifying discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Extensive efforts have been made to understand the frequently poor correspondence of experimental results between different species or between in vitro and in vivo studies [10,[29][30][31][32]. We have previously used our toxicogenomic approach to predict rat in vivo toxicity endpoints from rat in vitro RNA-seq data with good concordance [25].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive efforts have been made to understand the frequently poor correspondence of experimental results between different species or between in vitro and in vivo studies [10,[29][30][31][32]. We have previously used our toxicogenomic approach to predict rat in vivo toxicity endpoints from rat in vitro RNA-seq data with good concordance [25].…”
Section: Discussionmentioning
confidence: 99%
“…This technique is widely used to screen the toxicity of related RNA molecules and to elucidate the toxicity mechanisms ( 53 , 54 ). Biological analytes from environmental, industrial, and drug-induced toxic exposures have been analyzed using transcriptomics ( 54 61 ). Moreover, transcriptomics contributes to the comprehensive investigation of cellular responses induced by NPs using bioinformatics software ( 22 ).…”
Section: Recent Approaches For Metabolomics and Transcriptomics In Namentioning
confidence: 99%
“…For instance, in vivo, ex vivo and in vitro studies have found differing effects of stress on NK cell cytotoxicity [27]. Elsewhere, differing transcriptomics results between in vitro and in vivo toxicology studies pose a challenge for the pharmaceutical industry [28]. Lastly, cell migration patterns can differ substantially between in vivo and in vitro contexts [29].…”
Section: Diverse Sources For Model Parameter Values and Mechanicsmentioning
confidence: 99%